ANALISIS KARAKTERISTIK STRUKTUR MATERIAL SWING ARM TERHADAP RESPON GETARAN ACAK PADA SEPEDA MOTOR HONDA SUPRA X 125R MENGGUNAKAN METODE ELEMEN HINGGA - Winarno, Ilham; Marliana, Eka (POLITALA PRESS, 2023)
This research was conducted to determine the structural characteristics of each type of swing arm material of the Honda Supra X 125R motorcycle against random vibration responses. The random vibration response is modeled in modal analysis so that the value of natural frequency, maximum displacement, and correction factor that occurs can be identified. This research is based on FEM simulation by making 3D modeling using Autodesk Inventor software, which is then simulated using Ansys software. Based on the results of the FEM simulation, it was found that the most dominant mild steel material with the best response was SS400, with a maximum equivalent stress (von Mises) value of 16.601 MPa and a maximum displacement of 2.9109e–002 mm. The modal analysis results also show that the SS400 material has the most dominant response, with the highest average natural frequency in shapes 2, 4, and 5 modes, and has the smallest displacement value in shapes 1, 3, and 4 modes.